From FGFR2 mutations to precision management: a review of prenatal diagnosis and multidisciplinary interventions in apert syndrome - Li, Hong; Shen, Junling; Tang, Mei; Wan, Siran; Zhang, Shunhong (Frontiers in Pediatrics, 2025)
Apert syndrome is a severe autosomal dominant disorder caused by recurrent FGFR2 mutations, characterized by the prenatal triad of craniosynostosis, midface hypoplasia, and symmetric syndactyly. This review synthesizes evidence defining core sonographic features: turribrachycephaly secondary to bicoronal suture fusion, facial profile abnormalities including depressed nasal bridge and hypertelorism, and the distinctive “mitten hands/sock feet” syndactyly pattern best visualized via advanced 3D ultrasound in late gestation. Fetal MRI complements ultrasound by identifying associated intracranial anomalies and microstructural brain changes linked to neurodevelopmental outcomes. A definitive diagnosis relies on targeted FGFR2 sequencing. Prenatal identification of these features enables essential coordinated care, including thorough parental counseling, proactive perinatal planning for potential airway compromise, and coordinated neonatal care involving craniofacial, genetic, and neurodevelopmental specialists. The integration of structured imaging assessment with rapid molecular diagnostics facilitates a shift from passive anomaly identification to proactive, risk-stratified management, thereby optimizing the long-term functional prognosis through timely interventions.